2017
DOI: 10.1038/s41598-017-14053-0
|View full text |Cite
|
Sign up to set email alerts
|

Engraftment and morphological development of vascularized human iPS cell-derived 3D-cardiomyocyte tissue after xenotransplantation

Abstract: One of the major challenges in cell-based cardiac regenerative medicine is the in vitro construction of three-dimensional (3D) tissues consisting of induced pluripotent stem cell-derived cardiomyocyte (iPSC-CM) and a blood vascular network supplying nutrients and oxygen throughout the tissue after implantation. We have successfully built a vascularized iPSC-CM 3D-tissue using our validated cell manipulation technique. In order to evaluate an availability of the 3D-tissue as a biomaterial, functional morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 42 publications
(50 reference statements)
0
20
0
Order By: Relevance
“…Endothelial cells (ECs) have been included in myocardial tissue engineered constructs with the aim of in vitro vascularization; together with stromal cells, they improved the hPSC-derived tissue formation and vascular network growth in matrix-free scaffolds [ 61 ] and in a fibronectin-gelatine matrix [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Endothelial cells (ECs) have been included in myocardial tissue engineered constructs with the aim of in vitro vascularization; together with stromal cells, they improved the hPSC-derived tissue formation and vascular network growth in matrix-free scaffolds [ 61 ] and in a fibronectin-gelatine matrix [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…FN‐G nanofilms were formed onto the cell membranes of isolated hiPSC‐CM and NHCF using a filtration LbL method according to our previous report (Narita et al, ). The cells were suspended in 0.2 mg/ml FN from human plasma (Sigma‐Aldrich, MO) or G (Wako Pure Chemical Industries) in phosphate‐buffered saline (PBS; Wako Pure Chemical Industries), put into a six‐well culture insert with a 3 µm pore membrane (Corning) and shaken for 1 min at 500 rpm using MixMate shaker (Eppendorf).…”
Section: Layer‐by‐layer Cell Coating Methodsmentioning
confidence: 99%
“…In this study, we have constructed 3D cardiac tissues (LbL‐3D Heart) using a LbL cell coating method (Amano et al, ; Narita et al, ; Takeda et al, ) and a microscopic painting device using a painting needle method. Using the painting needle method, the biofabrication device can paint small amounts (several pl to several hundred nl) of bioinks over a wide viscosity range, (1 to 1 × 10 5 mPa·s) quickly (up to once every 0.1 s) and in high resolution.…”
Section: Introductionmentioning
confidence: 99%
“…7 Currently, iPS-derived cells have been applied for sickle cell anemia, PD, hemophilia A, and acute myocardial infarction in animal models. 8 Recently, Mandai et al reported that administered of iPSC derived retinal pigment epithelial (RPE) cells were used for the treatment of age related macular degeneration (AMD) in human. 9 Recent study suggested that iPSCs-NPCs (Neuronal progenitor cells) have potential efficacy for the treatment of chronic phase of SCI.…”
Section: Introductionmentioning
confidence: 99%